The Impact of Climate Change on European Tourism and Visitor Behavior - Suputra, I Gede Mas (Bali Tourism Board, 2025)
Tourism is one of Europe's most economically significant sectors, yet its dependence on stable climatic conditions renders it highly vulnerable to global warming. This study examines how climate change is reshaping European tourism patterns, visitor behavior, and destination management between 2021 and 2024. Using a qualitative content analysis of academic research, policy documents, and media reports, the paper synthesizes evidence on the environmental, behavioral, and institutional dimensions of adaptation. The findings reveal that climate change is driving both physical and behavioral transformations: alpine and Mediterranean destinations face mounting exposure to snow scarcity, heatwaves, and wildfires, while tourists increasingly display spatial, temporal, and qualitative adaptation—shifting toward cooler, higher-altitude, or off-peak destinations and favoring sustainable, experience-based travel. European destinations such as Berlin and Barcelona have begun adopting